2018
DOI: 10.1002/lary.27506
|View full text |Cite
|
Sign up to set email alerts
|

Office‐based laryngology: Technical and visual optimization by patient‐positioning maneuvers

Abstract: Objective/Hypothesis To qualitatively and quantitatively assess the effect of discrete head postures/maneuvers during flexible laryngoscopy on visualization of specific anatomical structures within the laryngopharynx. Study Design Prospective, observational study. Methods Flexible laryngoscopy was performed on 18 sequential patients. Videos of the laryngopharynx were captured during the neutral head position and five discrete maneuvers: maximal sniffing, head extension, right turn, left turn, and chin down. Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…While a variety of patient postures for awake transnasal flexible laryngoscopy exist in order to view the hypopharynx, glottis, esophageal inlet 4,5,12‐14 and more distal views, 6,7 the ability to adequately visualize the subglottis and proximal trachea in clinical practice is limited. This is the first single‐blinded prospective trial to evaluate the effect of patient posture on visualization of the subglottic and tracheal airways for in‐clinic laryngoscopy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While a variety of patient postures for awake transnasal flexible laryngoscopy exist in order to view the hypopharynx, glottis, esophageal inlet 4,5,12‐14 and more distal views, 6,7 the ability to adequately visualize the subglottis and proximal trachea in clinical practice is limited. This is the first single‐blinded prospective trial to evaluate the effect of patient posture on visualization of the subglottic and tracheal airways for in‐clinic laryngoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that simple forward head extension, or "sniffing" position, optimizes the view of the supraglottic and glottic structures. 4,5 Two studies describe the use of a flexed or "chin-tuck" head position to improve visualization of the distal airway in the awake patient. 4,6 Lastly, the laryngeal distraction or "stooping" maneuver, or chin tuck with head turn, has been implemented to obtain views of the subglottis and proximal trachea without the need for topical anesthetic administration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Office-based flexible transnasal laryngoscopy is a common routine procedure since many years. The development of new technical equipment such as flexible high-definition endoscopes allows for very precise examination [1][2][3][4][5][6][7][8][9]. The basic principle for getting optimal magnification in laryngoscopy is to decrease the distance of the lens to the target, i.e., the nearer one gets to the vocal fold, the more details one can see.…”
Section: Discussionmentioning
confidence: 99%